Abiotic reduction of nitrite by Fe(ii): a comparison of rates and N2O production. Issue 10 (13th September 2021) - Robinson, Thomas C.; Latta, Drew E.; Notini, Luiza; Schilling, Keith E.; Scherer, Michelle M.
Abstract : Nitrite reduction by Fe(ii ) in an agricultural sediment and complete conversion to N2 O suggests chemodenitrification is important to N2 O emissions. Abstract : Abiotic reduction of nitrite (NO2 − ) by Fe(ii ) species ( i.e., chemodenitrification) has been demonstrated in a variety of natural environments and laboratory studies, and is a potentially significant source of atmospheric nitrous oxide (N2 O) emissions. It is, however, unclear how chemodenitrification rates and N2 O yields vary among heterogeneous Fe(ii ) species under similar conditions and whether abiotic reduction competes with biological NO2 − reduction. Here, we measured rates of NO2 − reduction and extents of N2 O production by several Fe(ii ) species under consistent, environmentally relevant conditions ( i.e., pH 7.0, bicarbonate buffer, and 0.1 mM NO2 − ). Nitrite reduction rates varied significantly among the heterogeneous Fe(ii ) species with half-lives ( t 1/2 ) ranging from as low as an hour to over two weeks following the trend of goethite/Fe(ii ) ∼ hematite/Fe(ii ) ∼ magnetites > maghemite/Fe(ii ) > sediment/Fe(ii ). Interestingly, we observed no clear trend of increasing NO2 − reduction rates with higher magnetite stoichiometry ( x = Fe 2+ /Fe 3+ ). Nitrogen recovery as N2 O also varied significantly among the Fe species ranging from 21% to 100% recovery. We further probed both chemodenitrification and biological denitrification in the absence and presence of added aqueous Fe(ii ) with a sediment collected from the floodplain of an agricultural watershed. While abiotic NO2 − reduction by the sediment + Fe(ii ) was much slower than the laboratory Fe(ii ) species, we found near complete mass N balance during chemodenitrification, as well as evidence for both abiotic and biological NO2 − reduction potentially occurring in the sediment under anoxic conditions. Our results suggest that in redox active sediments and soils both chemodenitrification and biological denitrification are likely to occur simultaneously, and that agricultural watersheds may be significant sources of N2 O emissions.